Myths of trauma memory: on the oversimplification of effects of attention narrowing under stress - Davis, Deborah; Hogan, Alexis A.; Hart, Demi J. (Frontiers in Psychology, 2024)
For full guidelines please refer to Author Guidelines The present article addresses claims commonly made by prosecution witnesses in sexual assault trials: that attention narrows under stress, and that these attended aspects of the event are encoded in a way that ensures accuracy and resistance to fading and distortion. We provide evidence to contradict such claims. Given that what is encoded is the gist of one's interpretation of experience, we discuss the way in which attention and emotion can bias the interpretation of experience. We illustrate with issues of memory reports in cases of acquaintance rape, where the primary issue is the presence or absence of consent. We provide some specific illustrations concerning effects of emotion on interpretation of sexual consent. Finally, based on what is known regarding priming effects on memory retrieval and judgment, we conclude with discussion of the potential of some "trauma-informed" interviewing strategies to promote false memories (such as FETI: Forensic Experiential Trauma Interview).